Media Sosial Dan Perdebatan Politik: Upaya Gereja Mereduksi Konflik Pemilu di Era Digital Dalam Bingkai Etis Teologis - Yonatan Alex Arifianto; Jakson Sespa Toisuta (Sekolah Tinggi Teologi Blessing Indonesia Makassar, 2023)
This article aims to describe the important role of the church in theological ethics to deal with political conflicts that arise on social media during the election period in the digital era. Monitored debates on digital social media platforms create increasing political tensions and can trigger horizontal conflicts. The church therefore has the potential to play an important role in mitigating conflict and representing a more ethical dialogue. By using a theological ethical foundation, the church can provide a foundation and guide for values, reasoning and morals that are relevant to Christianity. Using descriptive qualitative methods with a literature study approach, it can be concluded that social media and political debate are the church's efforts to reduce election conflict in the digital era from an ethical and theological perspective. Firstly, Christianity can understand the importance of the nature of social media in politics and democratic parties so that with a theoretical study of the church and elections can foster theological ethical attitudes in the context of political debates where the church has a role in reducing election conflicts in the digital era.Keywords: Social Media; Political Debate; Reducing Conflict; Election; Digital era; Theological Ethical AbstrakArtikel ini bertujuan pentingnya peran gereja dalam etika teologis untuk menghadapi konflik politik yang muncul di media sosial selama masa pemilu di era digital. Perdebatan dalam platform digital media sosial yang terpantau membuat ketegangan politik yang semakin meningkat dan bisa memicu konflik horizontal. Dan tentunya gereja memiliki potensi untuk memainkan peran penting dalam meredakan konflik dan merepresentasikan dialog yang lebih etis. Dengan menggunakan landasan etika teologis, gereja dapat memberikan landasan dan panduan dari nilai dan nalar serta moral yang relevan bagi kekristenan. Menggunkan metode kualitatif deskritif dengan pendektan studi literature maka dapat disimpulkan bahwa media sosial dan perdebatan politik: upaya gereja mereduksi konflik pemilu di era digital dalam bingkai etis teologis, pertama kekristenan dapat memahami pentingnya hakikat media sosial dalam politik dan pesta demokrasi sehingga dengan kajian teortik gereja dan pemilu dapat menumbuhkan sikap etika teologis dalam konteks perdebatan politik yang mana gereja memiliki peran gereja dalam mereduksi konflik pemilu di era digital.